2017
DOI: 10.1097/bot.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Orthopaedic Trauma Patients

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…They also showed that patients with lower educational levels tended to have lower health literacy than those with higher educational levels [11]. Cosic et al showed that by providing a predischarge discussion with the patient to include a handout with an x-ray of the initial injury, x-rays of the operative fixation, and a small amount of written material describing the injury and ongoing management, it improved patient health literacy significantly [10]. Institutions have different protocols in place for both preoperative reading materials combined with postoperative instructions.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that patients with lower educational levels tended to have lower health literacy than those with higher educational levels [11]. Cosic et al showed that by providing a predischarge discussion with the patient to include a handout with an x-ray of the initial injury, x-rays of the operative fixation, and a small amount of written material describing the injury and ongoing management, it improved patient health literacy significantly [10]. Institutions have different protocols in place for both preoperative reading materials combined with postoperative instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Although general health literacy and musculoskeletal health literacy have been studied in the adult orthopedic population, there are very few studies which have examined the general and musculoskeletal health literacy of caregivers of pediatric orthopedic patients [23][24][25][26][27] . This is problematic as adequate health literacy allows caregivers to comprehend the medical knowledge needed to make informed decisions regarding the care of their children, and caregiver health literacy has been shown to directly impact pediatric outcomes in a variety of conditions [19,[28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…McCormack, Evoy, Mulcahy, and Walsh (1997) have previously shown that many patients willingly consent to acute orthopedic procedures that they do not fully understand, particularly with the use of orthopedic terminology such as “fracture reduction” and “internal fixation.” Although an element of consent and patient care can result from trust in the doctor-patient relationship, in current medical practice a lack of informed consent has medico-legal consequences, particularly if complications arise. Previous work has also found that orthopedic patients understand little of their injury, acute management, and ongoing treatment, which may have significant implications on patient compliance with management instructions and recovery (Cosic et al, 2017; Kadakia et al, 2013). Given that in the orthopedic setting, surgery forms only the initial management of an injury, it is essential to ensure patient compliance with ongoing management to achieve satisfactory outcomes for both patient and surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The key limitation of the study was the cross-sectional nature of the questionnaire, with an inability to follow up with patients at a later stage of their management to determine whether comprehension improved. However, given that the number of previous orthopedic encounters was not associated with patient comprehension, and that previous work has found that orthopedic outpatient review alone does not improve health literacy (Cosic et al, 2017), it is unlikely that patient comprehension improved after the questionnaire. Additionally, in this study we did not examine whether poor patient comprehension was associated with understanding of postoperative instructions or compliance to these instructions, and ultimately to orthopedic outcomes.…”
Section: Study Limitationsmentioning
confidence: 92%
See 1 more Smart Citation